Effects of Negative Emotions and Cognitive Characteristics on Impulse Buying During COVID-19 - Yu, Yongjuan (Frontiers in Psychology, 2022)
The COVID-19 pandemic has seriously disrupted the individual buying habits along with their consumption patterns. Previous studies indicated that anxiety and depression were related to impulse buying. However, no research has explored the mechanism possibly underlying the association between anxiety, depression, and impulse buying. Based on the regulatory focus theory and the emotion-cognition-behavior loop, this study aimed to examine the impacts of negative emotions on impulse buying and the mediating role of cognitive characteristics during the COVID-19 pandemic. In April 2021, 734 Chinese undergraduates were recruited by cluster sampling and they completed self-report measures of anxiety, depression, intolerance of uncertainty, cognitive flexibility, and impulse buying. Results showed that impulse buying was positively associated with anxiety, depression, and intolerance of uncertainty, while it was negatively associated with cognitive flexibility. Cognitive flexibility fully mediated the effects of anxiety and depression on cognitive facet of impulse buying. Meanwhile, intolerance of uncertainty fully mediated the effects of anxiety and depression on affective facet of impulse buying. Overall, this study shows that different pathways can explain how anxiety and depression exacerbate two aspects of impulse buying, and it highlights the importance of cognitive characteristics for the link between negative emotions and impulse buying. Intervention programs should focus on increasing cognitive flexibility and tolerance to uncertainty of high-risk individuals, so as to strengthen their adaptive purchase behaviors.